Treatment of lactating sows with clofibrate as a synthetic agonist of PPARalpha does not influence milk fat content and gains of litters - Gessner, Denise K.; Gröne, Birthe; Rosenbaum, Susann; Most, Erika; Hillen, Sonja; Becker, Sabrina; Erhardt, Georg; Reiner, Gerald; Eder, Klaus; Justus Liebig University Giessen (My University, 2015)
BACKGROUND: In rats, it has been observed that treatment with activators of peroxisome proliferator-activated receptor a (PPARalpha) disturbs metabolic adaptations during lactation, which in turn lead to a reduction of milk fat content and gains of litters during the suckling period. It has not yet been investigated whether agonists of PPARalpha are impairing milk production of lactating sows in a similar manner as in rats. Therefore, the present study aimed to investigate the effect of treatment with clofibrate, a strong synthetic agonist of PPARalpha, on milk composition and litter gains in lactating sows. RESULTS: Twenty lactating sows received either a basal diet (control group) or the same diet with supplementation of 2 g of clofibrate per kg of diet (clofibrate group). In the clofibrate group, mRNA concentrations of various PPARalpha target genes involved in fatty acid utilization in liver and skeletal muscle were moderately up-regulated. Fat and energy content of the milk and gains of litters during the suckling period were not different between the control group and the clofibrate group. CONCLUSIONS: It is shown that treatment with clofibrate induces only a moderate up-regulation of PPARalpha target genes in liver and muscle of lactating sows and in turn might have limited effect on whole body fatty acid utilization. This may be the reason why clofibrate treatment did not influence milk fat content and gains of litters during the suckling period. Thus, the present study indicates that activation of PPARalpha induced either by native agonists such as dietary polyunsaturated fatty acids or a by negative energy balance might be largely uncritical in lactating sows with respect to milk production and litter gains in lactating sows.
Keywords: ddc:630